Over-accumulation and Capitalism Collapse within Brazil in Review - Lima Botelho, Maurilio (Geografares, 2019)
The causes of the recent Brazilian crisis can not be search in “internal factors”, since the “national” economy has been integrated into the world economy since its modernization process. In a retrospective evaluation, which goes from the crisis of the so-called “neodevelopment” to the crisis of “economic miracle”, our main objective is to emphasize to Brazil’s intimate connection with the world economy, indicating that the current crisis is part of the failure of economic modernization Brazilian, which in turn is part of the structural crisis of capitalism.